The chemical composition of the Herbig Ae SB2 system AK Sco (HD 152404). Issue 2 (30th October 2019) - Castelli, F; Hubrig, S; Järvinen, S P; Schöller, M
ABSTRACT: We investigate the stellar atmospheres of the two components of the Herbig Ae SB2 system AK Sco to determine the elements present in the stars and their abundance. Equal stellar parameters T eff = 6500 K and g=4.5 were used for both stars. We studied HARPSpol spectra (resolution 110 000) that were previously used to state the presence of a weak magnetic field in the secondary. A composite synthetic spectrum was compared in the whole observed region λλ 3900–6912 Å with the observed spectrum. The abundances were derived mostly from unblended profiles, in spite of their sparsity, owing to the complexity of the system and to the not negligible v i of 18 and 21 km s −1 adopted for the two components, respectively. The identified elements are those typical of stars with spectral type F 5 IV-V, except for Li i at 6707 Å and He i at 5875.61 Å, whose presence is related with the Herbig nature of the two stars. Furthermore, overabundances were determined in both stars for Y, Ba, and La. Zirconium is overabundant only in the primary, while sulphur is overabundant outside the adopted error limits only in the secondary. In contrast to previous results showing a high occurrence rate of λ Boo peculiarities or normal chemical composition among the Herbig Ae/Be stars, the abundance pattern of AK Sco is similar to that of only few other Herbig stars displaying weak Ap/Bp peculiarities. A few accretion diagnostic lines are discussed.